The Statutory Right to Seek a Credit Contract Variation on the Grounds of Hardship: A History and Analysis. (2016) - Ali, Paul; Bourova, Evgenia; Ramsay, Ian
In this article, we focus on one of the most important statutory protections for Australian consumers in financial hardship: the right to seek a variation of a credit contract contained in s 72 of the National Credit Code. We provide a comprehensive history of this right, which has been part of Australian consumer credit law since the 1970s. Over the years, it has evolved from a very limited right to seek an extension of time to pay a debt on grounds of illness and unemployment, to a broader provision that requires credit providers to comply with a prescribed process before they can commence enforcement action against a consumer who has sought a variation to their payment arrangements. We also undertake an analysis of the evolution of this right to demonstrate that despite improved understandings of the causes of financial hardship, it continues to envisage a middle-class subject with a strong awareness of their rights, and excludes some particularly vulnerable consumers. This right is also representative of a regulatory approach that envisages a limited role for consumer credit law, and does not sufficiently address the imbalance of bargaining power between the consumer and the credit provider. We argue for the imposition of an obligation to provide a minimum range of hardship assistance directly upon credit providers, as a means of addressing this imbalance and ensuring more meaningful protection for consumers in financial hardship.